2022
DOI: 10.1002/ehf2.13971
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac involvement in patients recovering from Delta Variant of COVID‐19: a prospective multi‐parametric MRI study

Abstract: AimsThe cardiac injury and sequelae of Delta Variant of coronavirus disease 2019 remain unknown. This study aimed to evaluate the presence of cardiac involvement in patients recovering from Delta Variant of COVID-19 based on multiparametric cardiac magnetic resonance imaging (MRI). Methods and resultsWe prospectively assessed patients recovering from Delta Variant of COVID-19 using multi-parametric cardiac magnetic resonance imaging (MRI) between June 2021 and July 2021. Comparison was made with 25 healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…In patients recovered from COVID-19, cardiac involvement with ongoing inflammation on CMR has been described in patients with and without cardiac symptoms [ 12 , 13 , 25 ]. A recent study confirmed these findings in patients recovering from the Delta variant of COVID-19 [ 26 ]. In our study, none of the patients who underwent CMR showed cardiac involvement.…”
Section: Discussionsupporting
confidence: 55%
“…In patients recovered from COVID-19, cardiac involvement with ongoing inflammation on CMR has been described in patients with and without cardiac symptoms [ 12 , 13 , 25 ]. A recent study confirmed these findings in patients recovering from the Delta variant of COVID-19 [ 26 ]. In our study, none of the patients who underwent CMR showed cardiac involvement.…”
Section: Discussionsupporting
confidence: 55%
“…Fewer studies reported significantly higher ECV in patients who recovered from COVID-19, particularly those with a severe disease manifestation [27,31]. Other authors found similar values between recovered subjects and controls [4,29,30,32,41]. The pooled effect size for ECV measured at 1.5 T was -0.32 (95% CI -0.54 to -0.11) and was statistically significant (p = 0.0169).…”
Section: Parametric Mappingmentioning
confidence: 86%
“…Studies including patients who recovered from COVID-19 reported increased [4,27,28,33,35,36], slightly increased [29,32,38,39,41] or similar [31,34] T1 native mapping values compared to controls. In particular, Kotecha et al [28], Puntmann et al [35], and Thornton et al [37] found significantly higher T1 native mapping values in large groups of recovered subjects (148, 100 and 90, respectively) compared to different control groups, including patients without myocardial injury, healthy volunteers or controls, and risk factor-matched controls [26,28,35,37].…”
Section: Parametric Mappingmentioning
confidence: 97%
See 1 more Smart Citation
“…The correlation between myocardial injuries detected by troponin elevation and myocardial injury detected by imaging techniques such as cardiac resonance is also controversial. Abnormalities have been described in cardiac magnetic resonance performed in the subacute phase of the disease in patients in whom troponin elevations had not been detected in an acute phase, which is somewhat surprising [ 11 ].…”
mentioning
confidence: 99%